Removal of para-Phenylenediamine (PPD) Dye from Its Aqueous Solution by Adsorption Using the Activated Carbon Nanoparticles - Bdewi, Shabaa Fayyad; Hussein, Hanaa Hassan; Azeez, Shireen Abdulmohsin (Indonesian Journal of Chemistry, 2024)
This study focused on the development of an efficient preparation method of activated carbon for the removal of para-phenylenediamine (PPD) dye in an aqueous solution. Walnut shells, a readily accessible biomass source in northern Iraq, were processed into activated carbon (AC). Several techniques, such as FTIR, XRD, and SEM, were applied to describe and study the surface of AC. According to XRD analysis, all the reflection peaks with the relative intensities of various planes indicate that the obtained particle size was around 7.63 nm. The influences of contact time, adsorbent, and other variables (the thermodynamic parameters for the influence of temperature) were calculated after studying the dosage and initial concentration. The effects of the change in the acidity functions and the increasing temperature were also studied. The results found that the best adsorption occurred in 120 min, with a 0.1 g adsorbent substance weight and pH 5. The adsorption rate was at its best at a temperature of 318 K. The best-recorded adsorption rate was obtained when applying the Langmuir and Freundlich isotherms, and the adsorption processes were of a physical nature.